The Role of Artificial Intelligence and Electronic Intrusion Detection Systems in Protecting Solar Power Plants - Bozsik, Norbert; Bozsik, Nándor; Szeberényi, András (9th FEB International Scientific Conference: Sustainable Management in the Age of ESG and AI: Navigating Challenges and Opportunities, 2025)
The aim of the study is to show how the integration of artificial intelligence (AI) and electronic intrusion detection systems can contribute to increasing the security of solar power plants. The study analyses the use of smart camera systems, motion sensors, infrasound sensors and drone technology. The operation, benefits and integration potential of each technology are evaluated. The results show that AI-based systems significantly reduce false alarms, enable faster response and increase the effectiveness of security systems. Automated intrusion detection and drone-based surveillance facilitate proactive protection. The effectiveness of these systems can be affected by external environmental factors such as weather conditions, sensor maintenance requirements and the deployment of technological infrastructure. In addition, the use of AI may raise privacy and legal issues that need to be taken into account in its practical implementation. The results will contribute to safety engineering improvements and provide practical guidance for solar plant operators. AI-based systems create the potential for adaptive, self-improving security mechanisms that reduce human resource requirements and increase the reliability of security systems. The novelty of the research lies in the combined use of AI and electronic security, which allows for more effective operation of object protection systems.